Impact of Restaurant Attributes on Customer Perceived Value and Customer Satisfaction:: Special Reference to Beach Restaurants in Southern Coastal Area, Sri Lanka (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
Despite its popularity, the concept of customer satisfaction in the service industry in the marketing literature is still able to examine. The significant growth of the restaurant industry has made a strong contribution to the food and beverage sector in the hospitality industry. Modern customers are expecting broad experience from restaurants beyond food and beverages. Hence beach restaurants have been popularized all around the world. However, satisfying the customers has become challenging in the service sector like restaurant industry due to the high competition. It is essential to maintain particular attributes to create customer perceived value and ultimately satisfy the customers. This contemporary study has conducted to identify the impact of restaurant attributes on customer perceived value and customer satisfaction specifically in the beach restaurants in the Southern coastal area in Sri Lanka. Three hundred and eighty-five tourists who fulfilled their dining requirements at the beach restaurants in the Southern coastal area were selected using a convenient sampling technique and a self-administered questionnaire was fielded to collect primary data. Mediator analysis has conducted through Structural Equation Modelling (SEM) technique and SmartPLS software has used to analyze data. Five underlying factors were analyzed under restaurant attributes; of food and drink-related attributes, ambience and atmosphere related attributes, price-related attributes, location and place related attributes, and service-related attributes. The results reveal that the perceived value has the potential to be fully mediating variable between restaurant attributes and customer satisfaction in beach restaurants. Service providers of beach restaurants can enhance the uniqueness of restaurant attributes to enhance customer perceived value and ultimately it will enhance customer satisfaction as well.
Keywords: satisfaction; perceived-value; restaurant attributes; tourists; beach restaurants